Development and characterization of docetaxel and curcumin-loaded aerosolized nanoemulsion for pulmonary cancer - Asmawi, Azren Aida (2020)
Lung cancer tops the cancer mortality rate with the lowest survival rate among all the cancers. The synergistic anticancer effect of docetaxel (DTX) and curcumin (CCM) emerges as an attractive therapeutic candidate in lung cancer treatment. However, the lack of optimal bioavailability due to poor solubility, low stability, and high toxicity have limited their clinical success. Hence, attention has been focused on the use of inhalable nanoemulsion systems for pulmonary delivery to alleviate the drawbacks. In this study, DTX and CCM-loaded nanoemulsions were formulated and optimized using Mixture Experimental Design (MED) and Response Surface Methodology (RSM) emphasizing the criteria for pulmonary applications. The drug content was quantified using a newly developed and validated high-performance liquid chromatography (HPLC) method. The formulated nanoemulsions were then subjected to physicochemical and aerodynamical characterizations. Investigation of their efficacy and nanotoxicity was also evaluated. The MED model exhibited that the optimum formulation for DTX and CCM-loaded nanoemulsions containing palm kernel oil ester and safflower seed oil (1:1, w/w; 6.00%), lecithin (2.50%), Tween 85 and Span 85 (9:1, w/w; 2.00%), glycerol (2.50%), α-tocopherol (0.05%) and water (86.95%) was achieved. The formulations were prepared using different process parameters having targeted size of 100, 150, and 200 nm as predicted by the RSM models. The developed HPLC method showed specificity with high linearity, good precision, and accuracy which are consistent with the International Conference on Harmonization (ICH) guidelines. All nanoemulsions exhibited desirable pH, viscosity, conductivity, and surface tension attributes for pulmonary administration. The nebulized nanoemulsions were mainly deposited in the deep lung regions with aerodynamic size ranging from 2.8 to 3.3 μm and a high percentage of FPF (>75%). Their aerodynamic characteristics were governed by the size, surface tension, and viscosity of the nanoemulsions in an inverse proportion. The formulated nanoemulsions exhibited sustained drug release and excellent physical stability against extreme conditions for nanoemulsion with the size 100 nm compared to 150 and 200 nm due to the Ostwald ripening process. Interestingly, in-vitro and ex-vivo experiments revealed that the combination of DTX and CCM in the nanoemulsion system was to reduce nanotoxicity and synergistically increase the efficacy. Similar results were obtained in zebrafish acute toxicity study as the nanotoxicity of the nanoemulsions was found to be dose and particle size dependents, and combined DTX and CCM-loaded nanoemulsion exhibited higher LC50 value compared to single and free drug solutions. Hence, these characteristics make the formulation to be a great candidate for potential use as a carrier system for DTX and CCM in lung cancer treatment via pulmonary delivery.